Association between preoperative oxygen reserve index and postoperative pulmonary complications: a prospective observational study - Sangho Lee; Halin Hong; Hyojin Cho; Sang-Wook Lee; Ann Hee You; Hee Yong Kang; Sung Wook Park; Mi Kyeong Kim; Jeong-Hyun Choi (Korean Journal of Anesthesiology, 2025)
Background The oxygen reserve index (ORi) noninvasively measures oxygen levels within the mild hyperoxia range. To evaluate whether a degree of increase in the ORi during preoxygenation for general anesthesia is associated with the occurrence of postoperative pulmonary complications (PPCs). Methods We enrolled 154 patients who underwent preoperative pulmonary function tests and were scheduled for elective surgery under general anesthesia. We aimed to measure the increase in ORi during preoxygenation before general anesthesia and analyze its association with PPCs. Results PPCs occurred in 76 (49%) participants. Multivariate logistic regression analysis revealed that the three-minute preoxygenation ORi was significantly associated with PPCs (Odds ratio [OR]: 0.02, 95% CI [0.00–0.16], P < 0.001). The areas under the curve (AUC [95% CI]) in the receiver operating characteristic curve analysis for the three-minute preoxygenation ORi for PPCs were 0.64 (0.55–0.73). After a subgroup analysis, multivariate logistic regression showed that the three-minute preoxygenation ORi was significantly associated with PPCs among patients who underwent thoracic surgery (OR: 0.01, 95% CI [0.00–0.19], P = 0.006). The AUC of the three-minute preoxygenation ORi for PPCs was 0.72 (0.57–0.86) in patients who underwent thoracic surgery. Conclusions A low ORi measured after 3 min of preoxygenation for general anesthesia was associated with an increased risk of PPCs, including those undergoing thoracic surgery. This study demonstrated the potential of ORi, measured after oxygen administration, as a tool for evaluating lung function that complements traditional lung function tests and scoring systems.